1944
DOI: 10.1084/jem.80.4.299
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of the Type-Specific Polysaccharide of the Type I Meningococcus and a Study of Its Effectiveness as an Antigen in Human Beings

Abstract: The demonstration by Francis and Tillett (1) and others (2-5) that the typespecific polysaccharides of pneumococci are antigenic in man and induce the production of antibodies in humans which protect mice against subsequent injection of virulent organisms, has led to numerous attempts to use these purified polysaccharides in active immunization (4, 6). Since the antipolysaccharide in Type I antimeningococcal sera has also been found to be effective in protecting mice, the capacity of several preparations of Ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1955
1955
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Both the A and the C polysaccharides proved to be good immunogens in man. This result is at variance with previous experiments (7,8), but the polysaccharides tested prior to the present study were probably less than 50,000 average molecular weight (9). 1 It is our belief that the high molecular weight of the polysaccharides used in this study accounts for their immunogenicity, a hypothesis, which, however, has not been tested directly.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Both the A and the C polysaccharides proved to be good immunogens in man. This result is at variance with previous experiments (7,8), but the polysaccharides tested prior to the present study were probably less than 50,000 average molecular weight (9). 1 It is our belief that the high molecular weight of the polysaccharides used in this study accounts for their immunogenicity, a hypothesis, which, however, has not been tested directly.…”
Section: Discussionsupporting
confidence: 84%
“…Kabat et al (7) investigated the immunogenicity of the group A polysac. charide in human volunteers.…”
mentioning
confidence: 99%
“…In early attempts in the 1940s to prepare purified group A meningococcal PS vaccines, the PS was found to be almost nonimmunogenic (20). Later studies by Gotschlich et al (15) showed that the early failures were due to degradation of the PS.…”
Section: Ps Vaccinesmentioning
confidence: 99%
“…Roberts (250) reported that the anticapsular antibodies in serum against group A and C polysaccharides are responsible for most of the opsonic activity against meningococci. Kabat et al (169) in 1945 attempted to induce in human subjects antibody to meningococcal capsular polysaccharides, but failed, probably because of the small molecular weight of their preparations (<50,000 daltons), which failed to stimulate antibody. Gotschlich et al (124) developed an extraction and purification method that yielded polysaccharides from groups A, B, and C with molecular weights of >100,000.…”
Section: Meningococcal Surface Capsulesmentioning
confidence: 99%